2016
DOI: 10.5812/thrita.33411
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Two Educational Strategies on Knowledge, Attitude, Concerns, and Practices of Mothers With Febrile Convulsive Children

Abstract: Background: Febrile seizures are common during childhood and have a good prognosis, although they cause fear and anxiety in parents. Parent education is an important intervention in febrile seizures. Objectives: The aim of this study was to compare the effects of two educational strategies, written information vs. written information plus verbal instruction on knowledge, attitudes, concerns, and practices of mothers with febrile convulsive children. Patients and Methods: The study adopts a quasi-experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
5
6
1
2
Order By: Relevance
“…This result could be attributed to mothers' knowledge about importance of measuring temperature and controlling fever is the basic step in preventing and controlling febrile convulsion. This result was in an agreement with Barzegar et al [24] who stated that, most mothers take their children's temperature frequently during FC.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This result could be attributed to mothers' knowledge about importance of measuring temperature and controlling fever is the basic step in preventing and controlling febrile convulsion. This result was in an agreement with Barzegar et al [24] who stated that, most mothers take their children's temperature frequently during FC.…”
Section: Discussionsupporting
confidence: 82%
“…This result was in an agreement with Barzegar et al [24] who reported in his study that the majority of mothers believed that FC episode is a serious condition, can cause brain damage, can be increased and repeated, and more care and consideration are required for febrile convulsive children. In addition, the researcher also reported that, the pretest scores of mothers attitude toward febrile convulsion was low, while, post intervention there was significant improvement (p = .009) in the handout assemble group as compared with that of the control group.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Base on the report, the number of hemodialysis patients has been increasing by approximately 5% each year [9]. However, in a wide range of nursing intervention areas, hemodialysis patients are exposed to non-compliance risks [10,11]. Personalized nursing intervention is an effective tool to foster appropriate self-care management of patients while lowering healthcare treatment costs and to empower the patient of sick by improving their knowledge, attitudes, concerns, and practices regarding the illness [12,13].…”
Section: Introductionmentioning
confidence: 99%